Automated tree quantitative structure model (ATQSM) / Mohamad Amirul Hafiz Md Shukri, Zulkiflee Abd Latif and Nurul Ain Mohd Zaki - Md Shukri, Mohamad Amirul Hafiz; Abd Latif, Zulkiflee; Mohd Zaki, Nurul Ain (College of Built Environment, 2023)
An automated tree quantitative structure modelling (ATQSM) using Terrestrial Laser Scanning (TLS) is a technique to obtain forest information which is significant in estimating aboveground biomass (AGB) and carbon stock of tropical forests in Malaysia.